2004
DOI: 10.1089/1050725042451248
|View full text |Cite
|
Sign up to set email alerts
|

A New Assay for Thyrotropin Receptor Autoantibodies

Abstract: A new procedure for measuring patient serum thyrotropin receptor (TSHR) autoantibodies is described in which the autoantibodies inhibit binding of a human monoclonal thyroid stimulating antibody M22 (labeled with biotin) to TSHR-coated enzyme-linked immunosorbent assay (ELISA) plate wells. In the assay, M22-biotin binding is detected by addition of streptavidin peroxidase. The M22 based assay was more sensitive than a similar ELISA based on inhibition of TSH-biotin binding to TSHR coated wells with 1 U/L of NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 0 publications
5
79
1
Order By: Relevance
“…Interestingly, the AUC of the thirdgeneration TBII assay was 0.817 and that of the Mc4-TSI assay was 0.868, which means that both of these TRAb assays have equivalently high power in predicting severe GO disease course. Smith et al 12 showed the higher sensitivity of the M22-based ELISA than the TSH-based ELISA in diagnosing GD. The human monoclonal TSAb (M22) 9,10 allows a third-generation TBII assay system where the TRAb inhibits binding of a labeled TSAb rather than labeled TSH to the TSH receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the AUC of the thirdgeneration TBII assay was 0.817 and that of the Mc4-TSI assay was 0.868, which means that both of these TRAb assays have equivalently high power in predicting severe GO disease course. Smith et al 12 showed the higher sensitivity of the M22-based ELISA than the TSH-based ELISA in diagnosing GD. The human monoclonal TSAb (M22) 9,10 allows a third-generation TBII assay system where the TRAb inhibits binding of a labeled TSAb rather than labeled TSH to the TSH receptor.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most newly developed thirdgeneration TBII assay inhibits binding of a labeled TSAb (monoclonal Ab clone #M22) rather than labeled TSH to the TSH receptor 9,10 This results in enhanced sensitivity and specificity vs earlier assays using radiolabeled TSH. 6,8,11,12 The TSI bioassay measures cyclic adenosine monophosphate production after TSAb binds to TSH receptor. [13][14][15] Thus, this method enables the identification of the functional characteristics of TRAb.…”
Section: Introductionmentioning
confidence: 99%
“…Assays used in clinical routine differ considerably in their ability to detect such antibodies (4,5), but recent generations of assays show high sensitivity and specificity (14,15). In the present study, TRAb was measured using a radioreceptor assay that was able to detect TRAb in 83% of the untreated patients.…”
Section: Discussionmentioning
confidence: 92%
“…In this method, 125 I-labeled bovine TSH compete with TRAb in serum samples to bind to purified porcine TSH receptors, followed by polyethylene glycol precipitation (13). After the completion of our study, new generations of TRAb assays have been developed (14,15), and it has been shown that a minor subset of sera from patients with Graves' disease are falsely negative using the assay employed in our study (15). For the present calculations and presentation of results, we included only patients who were TRAb-positive at the time of inclusion in the study and before therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a new method for measuring TRAb has been described by Rees Smith [31], in which autoantibodies inhibit the binding of a human thyroid-stimulating mAb M22 [32] labelled with biotin to TSHR-coated ELISA plate wells. The method is called the manual third-generation TRAb assay.…”
Section: Introductionmentioning
confidence: 99%